FAKTOR RISIKO MUSKULOSKELETAL DISORDERS (MSDS) PADA PEKERJA PENYORTIR SAMPAH DI UPTD PENGELOLAAN SAMPAH TALANG GULO - Rahmat Faisal; Rara Marisdayana; Eti Kurniawati (Sekolah Tinggi Pariwisata Mataram, 2022)
Musculoskeletal is a problem caused by stretching of the muscles and skeleton, if not treated immediately, it will interfere with concentration at work, causing fatigue and ultimately reducing productivity. The research design used was cross sectional. The sample of the study was 26 people in the waste sorting unit at the UPTD Talang Gulo waste management. The research instrument is a questionnaire. Data were analyzed using Kendall's tau-b correlation statistic test. The results showed that there was a significant correlation between attitudes (p=0.026), repetitive activities (p=0.007) with complaints of musculoskeletal disorders (MSDs) in the waste sorter workers at the UPTD for waste management in Talang Gulo. There was no relationship between age (p=0.894) and complaints of musculoskeletal disorders (MSDs) in waste sorting workers at the UPTD for waste management in Talang Gulo. From these results, it can be concluded that the complaints of musculoskeletal disorders in the waste sorter workers at the UPTD Talang Gulo waste management are related to repetitive attitudes and activities. It is recommended for workers to pay attention to body posture when working according to ergonomic principles, then when working it is necessary to pay attention to body posture so that they can work comfortably, so that work attitudes do not risk the occurrence of musculoskeletal disorders.